The ABCs of Law - Remy Llerena, Gastón Roger (2021)
The law is one of the fundamental creations for the social nature of man and is one of the great civilizing forces that helped and helps the person to reach degrees of sophistication. The law is generally linked to the gradual growth of a system of legal norms next to a machine that allows constant and effective implementation. The law does not exist in a vacuum, but coexists with moral codes of varying complexity or degree of accuracy. Also the relationship that the law keeps principled certainly has a huge and continuing importance in our society as evidenced by many current cases. The notion we have of the law is that itis a rule of conduct imposed on men living in society and respect for which is ensured by the public authority. On the right term it is implied the idea of a rule (directum) and this image is in modern languages. Moreover, the rule of law is not the only rule of life in society and many other social rules are imposed by religion, by the laws of morality; for the purposes of society. In the present article deals with the law, both in its external and formal aspect, either within content, its basis and purpose.